Music in Lichhavi and Malla Period: An Overview - Pokharel, Ramesh (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
Music is a universal language which transcends all barriers of country, race or religion. The people of Nepal are immensely music oriented. This paper attempts to discuss the music conditions during Lichchhavi and Malla periods of Nepal in relation to development, extension and its practices in Nepalese society. All evidences have been taken from several documentaries. Whatever we practice as traditional Music today has taken the step of development in this very age. The evidence shows that specially raga based traditional Music was practiced in those periods.